CRISIS DEL PETRÓLEO Y POLÍTICA ENERGÉTICA - Narváez Liceras, Alejandro (2006)
It is expected a growth in the production production high growth in developed countries distinguished by high energy consumption and this trend is also increasingly. In this scenary, a national energy policy which reduces vulnerabilities in our economy, permits to do savings in energy consumption and promote production and technological diversification, must consider energy security as main priority in order to guarantee a sustained development in the future and to reach the challenge of an energy autosufficiency; enviromental conservation through the promotion and development of renewable energy projects; investment in energetic efficiency and finally the modernization and strengthen of Petroperú. These policies imply a focus change from short term to the medium and long term in the management of our resources.